Les arrangements pour l’accès au foncier agricole périurbain - Camille Clément; Coline Perrin; Christophe-Toussaint Soulard (Développement Durable et Territoires, 2019)
The article deals with the farmland access issue on urban fringes. Taking a legal geography approach, it presents the results of a survey of 17 farms near Montpellier. More than a third of the surveyed areas are exploited by informal arrangements. The tenant farming who protects a lot the farmer does not cover these contracts. These informal contracts develop in particular the wheat/melon, leisure horses and rangeland sectors. The spaces linked to these arrangements come from the wine crisis, from the anticipation of urbanization, but also from the older crisis of pastoral sector. Arrangements illustrate the local production of a social norm bypassing the tenant farming rule. Winemakers are often landowners. They dominate the local land tenure system. Arrangements, giving them the power to control their cultivated lands by others and lead to the exclusion of non-socially integrated farmers.